New-generation triazole antifungal drugs: review of the Phase II and III trials. (November 2011) - Girmenia, Corrado; Finolezzi, Erica
In this article, the pharmacological, microbiological and clinical development progress from Phase II and III clinical trials with the new generation triazoles albaconazole, isavuconazole, posaconazole, ravuconazole and voriconazole are reviewed. These drugs exhibit a favorable toxicity profile and possess high activity against resistant and emerging fungal pathogens. Pharmacokinetic may be affected by variability in metabolism and/or gastrointestinal absorption. Only voriconazole and posaconazole have been adequately investigated and are now indicated in the treatment and prophylaxis of invasive fungal diseases. Other triazoles; albaconazole, isavuconazole and ravuconazole are under development; therefore, their future use is unknown.